2016
DOI: 10.1187/cbe.16-01-0072
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Peer Review and a Multisemester Capstone Writing Series on Inquiry and Analysis Skills in an Undergraduate Thesis

Abstract: This study demonstrates the positive impact of peer review and a multisemester writing capstone on inquiry, science literacy, and critical thinking skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 34 publications
(80 reference statements)
0
15
0
Order By: Relevance
“…Performance benefits of student peer-review activities include the development of evaluation, critical thinking, written expression and other transferrable skills. Weaver et al (2016) demonstrate an increase in student performance in the areas of science literacy and critical thinking as a result of peer-review activities in a biology research course. In their analysis of peer-review activities in a critical skills course, Tighe-Mooney et al (2016, p14) identified the development of 'critical skills including, analysis and evaluation, making judgments and providing evidence and support for decisions made' as well as improvements in the ability to 'communicate, both in writing and verbally, to actively give and receive feedback, as well as reflect on the process and their input into it.'…”
Section: The Benefits Of Peer-reviewmentioning
confidence: 90%
“…Performance benefits of student peer-review activities include the development of evaluation, critical thinking, written expression and other transferrable skills. Weaver et al (2016) demonstrate an increase in student performance in the areas of science literacy and critical thinking as a result of peer-review activities in a biology research course. In their analysis of peer-review activities in a critical skills course, Tighe-Mooney et al (2016, p14) identified the development of 'critical skills including, analysis and evaluation, making judgments and providing evidence and support for decisions made' as well as improvements in the ability to 'communicate, both in writing and verbally, to actively give and receive feedback, as well as reflect on the process and their input into it.'…”
Section: The Benefits Of Peer-reviewmentioning
confidence: 90%
“…This could also offer opportunities to illuminate how actions and new insights might be realised in the intersection of abstract knowledge resources and practical situations. Weaver et al (2016) recognised the importance of writing as a tool for developing inquiry and analytical skills in IBL. They argue that writing is a tool for learning, and students who write down their IBL results build connections between prior and new knowledge.…”
Section: How Does Ibl Support and Enhance Student Learning?mentioning
confidence: 99%
“…), so make sure that their writing and presentations meet high standards. Concept mapping, outlines, annotated bibliographies, and peer-reviews can help frame writing projects, and there is a growing body of literature on their effectiveness in student learning [ 32 35 ]. Set reasonable deadlines that will allow you to work with students on reviews, revisions, flaws in logic, and style.…”
Section: What Is a Start-up Package?mentioning
confidence: 99%